O historiador diante de seu duplo : Ferdinand Adolf Gregorovius e a estética romântica na construção da biografia Lucrecia Bórgia (1874) - Vieira, Jéssika Hingridi Rodrigues (2016)
This paper discusses about the historiography written by the German historian Ferdinand Adolf Gregorovius (1821-1891). Known as "a bitter enemy of the popes", Gregorovius has an important historical production for historians of the medieval Papacy and Renaissance. In this research we worked through a specific historical work, writing biography of one of the most polemics ladies of the Renaissance: Lucrezia Borgia. The biography in question is entitled Lucrezia Borgia according to Original Documents and Correspondence of Her Day, published in German by Gregorovius in 1874. To compose is dissertation also use other complementary source: the Diaries written by Gregorovius between the years 1852 and 1874. We used the London edition of George Bell & Sons published in 1907, called The Roman Journals of Ferdinand Gregorovius. In this edition we rely primarily from the 70s onwards, as are the notes that were related to the exercise of the biography of Lucrezia Borgia. Our research aims working with the hypothesis that this narrative is composed by a symbiosis between the historiographical writing and aesthetic elements of literature. On these aesthetic elements present in the biography dedicated by Ferdinand Adolf Gregorovius to Lucrezia Bórgia we find an appropriate concept in sociological theory of the novel by the Hungarian philosopher Georg Lukács. In writing Gregorovius we identified two central aesthetic categories: the conflict between the individual and degraded the social totality, summing up the world of Lucrezia to the Papacy, and the characterization of Lucrezia as a hopelessly degraded social trajectory. Furthermore, we show that the size of individual combat against social totality and social degradation, attributed to Lucrezia Borgia, can be explained as a literary projection of the author’s life, Ferdinand Gregorovius. Therefore, considering the main source of daily Gregorovius, we will investigate how these aspects of bourgeois subjectivity are compositions of the author's own subjectivity, represented in historiographical terms in the figure of the protagonist of his biography.